The Effect of Propolis in Healing Injured Nasal Mucosa: An Experimental Study - El-Anwar,MohammadWaheed (2016)
Abstract Introduction Mechanical trauma to the nasal mucosa increases the risk of synechia formation, especially after chronic rhinosinusitis and nasal surgeries. Objective This study was carried to assess the effect of propolis administration in healing injured nasal mucosa in rats. Methods We randomly divided eighteen rats into three equal experimental groups: (1) non-treated group; (2) gum tragacanth (suspending agent for propolis) treated group; and (3) propolis treated group. The non-treated group received no treatment for 15 days. The second group received gum tragacanth administration (5 ml/kg, orally) once daily for 15 days. The third group received propolis suspension orally at a dose of 100 mg/kg once daily for 15 days. At the beginning of this study, we induced unilateral mechanical nasal trauma on the right nasal mucosa of all rats in the three groups using a brushing technique. A pathologist stained tissue samples using hematoxylin and examined eosin by using a light microscope. Results The severity of inflammation wasmilder with the absence of ulcerations in the propolis treated group compared with the non-treated and gum tragacanth groups. Goblet cell and ciliated cell loss was substantially lower in patients treated with propolis compared with groups without treatment and those treated with gum tragacanth. Conclusion Propolis decreased inflammation and enhanced healing of wounds of the nasal mucosa in rats.